2022
DOI: 10.1101/2022.11.08.515543
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Melanocortin 1 receptor regulates cholesterol and bile acid metabolism in the liver

Abstract: Melanocortin 1 receptor (MC1-R) is widely expressed in melanocytes and leukocytes, and is thus strongly implicated in the regulation of skin pigmentation and inflammation. MC1-R mRNA has also been found in the rat and human liver, but its functional role has remained elusive. We hypothesized that MC1-R is functionally active in the liver and involved in the regulation of cholesterol and bile acid metabolism. We generated hepatocyte-specific MC1-R knock-out (L-Mc1r-/-) mice and phenotyped the mouse model for li… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 60 publications
(65 reference statements)
2
3
0
Order By: Relevance
“…This view is also supported by previous studies, which have shown that MC1R activation does not have a signi cant effect on lipid metabolism in cultured adipocytes (17). Furthermore, our recent study revealed that hepatic MC1R signaling regulates cholesterol and bile acid metabolism in mice (19), indicating existence of functional MC1R in the liver.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This view is also supported by previous studies, which have shown that MC1R activation does not have a signi cant effect on lipid metabolism in cultured adipocytes (17). Furthermore, our recent study revealed that hepatic MC1R signaling regulates cholesterol and bile acid metabolism in mice (19), indicating existence of functional MC1R in the liver.…”
Section: Discussionsupporting
confidence: 86%
“…Besides susceptibility for increased hepatic TG accumulation, Western diet-fed Mc1r LKO mice exhibited signs of enhanced liver brosis and in ammation as well as apoptosis. We had previously observed that selective activation of MC1R had no effect on in ammatory markers but reduced the expression of brosis-associated genes in cultured hepatocytes (19). In the current study, we extend this knowledge by showing that MC1R activation has some direct effects on apoptotic markers in primary hepatocytes.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…BAs typically performs its function through BA receptors ( 36 ). The major forms of BA receptors (BA membrane receptors and nucleic receptors) were depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%